Kanon og glemsel – Arkæologiens mindesmærker - Wienberg, Jes (Kuml, 2007)
Canon and oblivion. The memorials of archaeology The article takes its point of departure in the sun chariot; the find itself and its find site at Trundholm bog where it was discovered in 1902. The famous sun chariot, now at the National Museum in Copenhagen, is a national treasure included in the Danish “Cultural Canon” and “History Canon”. The find site itself has alternated between experiencing intense attention and oblivion. A monument was erected in 1925; a new monument was then created in 1962 and later moved in 2002. The event of 1962 was followed by ceremonies, speeches and songs, and anniversary celebrations were held in 2002, during which a copy of the sun chariot was sacrificed. The memorial at Trundholm bog is only one of several memorials at archaeological find sites in Denmark. Which finds have been commemorated and marked by memorials? When did this happen? Who took the initiative? How were they executed? Why are these finds remembered? What picture of the past do we meet in this canon in stone? Find sites and archaeological memorials have been neglected in archaeology and by recent trends in the study of the history of archaeology. Considering the impressive research on monuments and monumentality in archaeology, this is astonishing. However, memorials in general receive attention in an active research field on the use of history and heritage studies, where historians and ethnologists dominate. The main focus here is, however, on war memorials. An important source of inspiration has been provided by a project led by the French historian Pierre Nora who claims that memorial sites are established when the living memory is threatened (a thesis refuted by the many Danish “Reunion” monuments erected even before the day of reunification in 1920). Translated into Danish conditions, studies of the culture of remembrance and memorials have focused on the wars of 1848-50 and 1864, the Reunion in 1920, the Occupation in 1940-45 and, more generally, on conflicts in the borderland between Denmark and Germany. In relation to the total number of memorials and public meeting places in Denmark, archaeological memorials of archaeology are few in number, around 1 % of the total. However, they prompt crucial questions concerning the use of the past, on canon and oblivion. “Canon” means rule, and canonical texts are the supposed genuine texts in the Bible. The concept of canon became a topic in the 1990s when Harold Bloom, in “The Western Canon”, identified a number of books as being canonical. In Denmark, canon has been a great issue in recent years with the appearance of the “Danish Literary Canon” in 2004, and the “Cultural Canon” and the “History Canon”, both in 2006. The latter includes the Ertebølle culture, the sun chariot and the Jelling stone. The political context for the creation of canon lists is the so-called “cultural conflict” and the debate concerning immigration and “foreigners”. Canon and canonization means a struggle against relativism and oblivion. Canon means that something ought to be remembered while something else is allowed to be forgotten. Canon lists are constructed when works and values are perceived as being threatened by oblivion. Without ephemerality and oblivion there is no need for canon lists. Canon and oblivion are linked. Memorials mean canonization of certain individuals, collectives, events and places, while others are allowed to be forgotten. Consequently, archaeological memorials constitute part of the canonization of a few finds and find sites. According to Pierre Nora’s thesis, memorials are established when the places are in danger of being forgotten. Whether one likes canon lists or not, they are a fact. There has always been a process of prioritisation, leading to some finds being preserved and others discarded, some being exhibited and others ending up in the stores. Canonization is expressed in the classical “Seven Wonders of the World”, the “Seven New Wonders of the World” and the World Heritage list. A find may be declared as treasure trove, as being of “unique national significance” or be honoured by the publication of a monograph or by being given its own museum. In practice, the same few finds occur in different contexts. There seems to be a consensus within the subject of canonization of valuing what is well preserved, unique, made of precious metals, bears images and is monumental. A top-ten canon list of prehistoric finds from Denmark according to this consensus would probably include the following finds: The sun chariot from Trundholm, the girl from Egtved, the Dejbjerg carts, the Gundestrup cauldron, Tollund man, the golden horns from Gallehus, the Mammen or Bjerringhøj grave, the Ladby ship and the Skuldelev ships. Just as the past may be used in many different ways, there are many forms of memorial related to monuments from the past or to archaeological excavations. Memorials were constructed in the 18th and 19th centuries at locations where members of the royal family had conducted archaeology. As with most other memorials from that time, the prince is at the centre, while antiquity and archaeology create a brilliant background, for example at Jægerpris (fig. 2). Memorials celebrating King Frederik VII were created at the Dæmpegård dolmen and at the ruin of Asserbo castle. A memorial celebrating Count Frederik Sehested was erected at Møllegårdsmarken (fig. 3). Later there were also memorials celebrating the architect C.M. Smith at the ruin of Kalø Castle and Svend Dyhre Rasmussen and Axel Steensberg, respectively the finder and the excavator of the medieval village at Borup Ris. Several memorials were erected in the decades around 1900 to commemorate important events or persons in Danish history, for example by Thor Lange. The memorials were often located at sites and monuments that had recently been excavated, for example at Fjenneslev (fig. 4). A large number of memorials commemorate abandoned churches, monasteries, castles or barrows that have now disappeared, for example at the monument (fig. 5) near Bjerringhøj. Memorials were erected in the first half of the 20th century near large prehistoric monuments which also functioned as public meeting places, for example at Glavendrup, Gudbjerglund and Hohøj. Prehistoric monuments, especially dolmens, were also used as models when new memorials were created during the 19th and 20th centuries. Finally, sculptures were produced at the end of the 19th century sculptures where the motif was a famous archaeological find – the golden horns, the girl from Egtved, the sun chariot and the woman from Skrydstrup. In the following, this article will focus on a category of memorials raised to commemorate an archaeological find. In Denmark, 24 archaeological find sites have been marked by a total of 26 monuments (fig. 6). This survey is based on excursions, scanning the literature, googling on the web and contact with colleagues. The monuments are presented chronological, i.e. by date of erection. 1-2) The golden horns from Gallehus: Found in 1639 and 1734; two monuments in 1907. 3) The Snoldelev runic stone: Found in c. 1780; monument in 1915. 4) The sun chariot from Trundholm bog: Found in 1902; monument in 1925; renewed in 1962 and moved in 2002. 5) The grave mound from Egtved: Found in 1921; monument in 1930. 6) The Dejbjerg carts. Found in 1881-83; monument in 1933. 7) The Gundestrup cauldron: Found in 1891; wooden stake in 1934; replaced with a monument in 1935. 8) The Bregnebjerg burial ground: Found in 1932; miniature dolmen in 1934. 9) The Brangstrup gold hoard. Found in 1865; monument in 1935. 10-11) Maglemose settlements in Mullerup bog: Found in 1900-02; two monuments in 1935 and 1936. 12) The Skarpsalling vessel from Oudrup Heath: Found in 1891; monument in 1936. 13) The Juellinge burial ground: Found in 1909; monument in 1937. 14) The Ladby ship: Found in 1935; monument probably in 1937. 15) The Hoby grave: Found in 1920; monument in 1939. 16) The Maltbæk lurs: Found in 1861 and 1863; monument in 1942. 17) Ginnerup settlement: First excavation in 1922; monument in 1945. 18) The golden boats from Nors: Found in 1885; monument in 1945. 19) The Sædinge runic stone: Found in 1854; monument in 1945. 20) The Nydam boat: Found in 1863; monument in 1947. 21) The aurochs from Vig: Found in 1904; monument in 1957. 22) Tollund Man: Found in 1950; wooden stake in 1968; renewed inscription in 2000. 23) The Veksø helmets: Found in 1942; monument in 1992. 24) The Bjæverskov coin hoard. Found in 1999; monument in 1999. 25) The Frydenhøj sword from Hvidovre: Found in 1929; monument in 2001; renewed in 2005. 26) The Bellinge key: Found in 1880; monument in 2003. Two monuments (fig. 7) raised in 1997 at Gallehus, where the golden horns were found, marked a new trend. From then onwards the find itself and its popular finders came into focus. At the same time the classical or old Norse style of the memorials was replaced by simple menhirs or boulders with an inscription and sometimes also an image of the find. One memorial was constructed as a miniature dolmen and a few took the form of a wooden stake. The finds marked by memorials represent a broader spectrum than the top-ten list. They represent all periods from the Stone Age to the Middle Ages over most of Denmark. Memorials were created throughout the 20th century; in greatest numbers in the 1930s and 1940s, but with none between 1968 and 1992. The inscriptions mention what was found and, in most cases, also when it happened. Sometimes the finder is named and, in a few instances, also the person on whose initiative the memorial was erected. The latter was usually a representative part of the political agency of the time. In the 18th and 19th centuries it was the royal family and the aristocracy. In the 20th century it was workers, teachers, doctors, priests, farmers and, in many cases, local historical societies who were responsible, as seen on the islands of Lolland and Falster, where ten memorials were erected between 1936 and 1951 to commemorate historical events, individuals, monuments or finds. The memorial from 2001 at the find site of the Frydenhøj sword in Hvidovre represents an innovation in the tradition of marking history in the landscape. The memorial is a monumental hybrid between signposting and public art (fig. 8). It formed part of a communication project called “History in the Street”, which involved telling the history of a Copenhagen suburb right there where it actually happened. The memorials marking archaeological finds relate to the nation and to nationalism in several ways. The monuments at Gallehus should, therefore, be seen in the context of a struggle concerning both the historical allegiance and future destiny of Schleswig or Southern Jutland. More generally, the national perspective occurs in inscriptions using concepts such as “the people”, “Denmark” and “the Danes”, even if these were irrelevant in prehistory, e.g. when the monument from 1930 at Egtved mentions “A young Danish girl” (fig. 9). This use of the past to legitimise the nation, belongs to the epoch of World War I, World War II and the 1930s. The influence of nationalism was often reflected in the ceremonies when the memorials were unveiled, with speeches, flags and songs. According to Marie Louise Stig Sørensen and Inge Adriansen, prehistoric objects that are applicable as national symbols, should satisfy three criteria. The should: 1) be unusual and remarkable by their technical and artistic quality; 2) have been produced locally, i.e. be Danish; 3) have been used in religious ceremonies or processions. The 26 archaeological finds marked with memorials only partly fit these criteria. The finds also include more ordinary finds: a burial ground, settlements, runic stones, a coin hoard, a sword and a key. Several of the finds were produced abroad: the Gundestrup cauldron, the Brangstrup jewellery and coins and the Hoby silver cups. It is tempting to interpret the Danish cultural canon as a new expression of a national use of the past in the present. Nostalgia, the use of the past and the creation of memorials are often explained as an expression of crisis in society. This seems reasonable for the many memorials from 1915-45 with inscriptions mentioning hope, consolation and darkness. However, why are there no memorials from the economic crisis years of the 1970s and 1980s? It seems as if the past is recalled, when the nation is under threat – in the 1930s and 40s from expansive Germany – and since the 1990s by increased immigration and globalisation. The memorials have in common local loss and local initiative. A treasure was found and a treasure was lost, often to the National Museum in Copenhagen. A treasure was won that contributed to the great narrative of the history of Denmark, but that treasure has also left its original context. The memorials commemorate the finds that have contributed to the narrative of the greatness, age and area of Denmark. The memorials connect the nation and the native place, the capital and the village in a community, where the past is a central concept. The find may also become a symbol of a region or community, for example the sun chariot for Trundholm community and the Gundestrup cauldron for Himmerland. It is almost always people who live near the find site who want to remember what has been found and where. The finds were commemorated by a memorial on average 60 years after their discovery. A longer period elapsed for the golden horns from Gallehus; shortest was at Bjæverskov where the coin hoard was found in March 1999 and a monument was erected in November of the same year. Memorials might seem an old-fashioned way of marking localities in a national topography, but new memorials are created in the same period as many new museums are established. A unique find has no prominent role in archaeological education, research or other work. However, in public opinion treasures and exotic finds are central. Folklore tells of people searching for treasures but always failing. Treasure hunting is restricted by taboos. In the world of archaeological finds there are no taboos. The treasure is found by accident and in spite of various hindrances the find is taken to a museum. The finder is often a worthy person – a child, a labourer or peasant. He or she is an innocent and ordinary person. A national symbol requires a worthy finder. And the find occurs as a miracle. At the find site a romantic relationship is established between the ancestors and their heirs who, by way of a miracle, find fragments of the glorious past of the nation. A paradigmatic example is the finding of the golden horns from Gallehus. Other examples extend from the discovery of the sun chariot in Trundholm bog to the Stone Age settlement at Mullerup bog. The article ends with a catalogue presenting the 24 archaeological find sites that have been marked with monuments in present-day Denmark. Jes Wienberg Historisk arkeologi Institutionen för Arkeologi och Antikens historia Lunds Universitet